2021
DOI: 10.3171/2020.8.jns202431
|View full text |Cite
|
Sign up to set email alerts
|

Stereoelectroencephalographic language mapping of the basal temporal cortex predicts postoperative naming outcome

Abstract: OBJECTIVEIn drug-resistant temporal lobe epilepsy (TLE) patients, the authors evaluated early and late outcomes for decline in visual object naming after dominant temporal lobe resection (TLR) according to the resection status of the basal temporal language area (BTLA) identified by cortical stimulation during stereoelectroencephalography (SEEG).METHODSTwenty patients who underwent SEEG for drug-resistant TLE met the inclusion criteria. During language mapping, a site was considered positive when stimulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Neuropsychological deficit-lesion mapping showed a significant association of naming decline and resection of the ventral temporal neocortex in the area of the ITG and FG, an area corresponding to the basal temporal language area (BTLA) localized in the dominant hemisphere. Delineated by electrical cortical stimulation, this language area has an extension of 10 to 90 mm posterior to the temporal pole, comprising the ITG, FG, and parahippocampal gyrus ( Krauss et al, 1996 , Abdallah et al, 2021 ). Electrical cortical stimulation in the middle FG only disrupted naming in isolation, while other tasks, like the ability to repeat sentences, were preserved ( Forseth et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropsychological deficit-lesion mapping showed a significant association of naming decline and resection of the ventral temporal neocortex in the area of the ITG and FG, an area corresponding to the basal temporal language area (BTLA) localized in the dominant hemisphere. Delineated by electrical cortical stimulation, this language area has an extension of 10 to 90 mm posterior to the temporal pole, comprising the ITG, FG, and parahippocampal gyrus ( Krauss et al, 1996 , Abdallah et al, 2021 ). Electrical cortical stimulation in the middle FG only disrupted naming in isolation, while other tasks, like the ability to repeat sentences, were preserved ( Forseth et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lüders et al identified a basal temporal language area (BTLA) as a language processing area, mainly responsible for confrontational naming ( Lüders et al, 1991 ). The BTLA was delineated by high-frequency cortical stimulation during stereo-EEG 10 to 90 mm from the temporal pole, primarily located in the fusiform gyrus, extending into the parahippocampal gyrus, the inferior temporal gyrus, and the occipito-temporal sulcus ( Krauss et al, 1996 , Bédos Ulvin et al, 2017 , Abdallah et al, 2021 ). Studies applying fMRI showed functional connectivity of the area around the gyrus fusiformis with attentional, visual and auditoy-sensory, lexical semantic processing, and articulation, reflecting the involvement in a language network ( Binder et al, 2009 , Forseth et al, 2018 , Chen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, studies which report substantial naming declines often test patients 4–7 months post-surgery ( Binder et al, 2020 , Busch et al, 2016 , Trimmel, 2019 ) whereas our patients were tested an average of 15 months post-surgically. Given that greater naming declines may occur earlier in the postoperative period ( Langfitt and Rausch, 1996 ) and that two studies report decline in the first 6 months followed by an improvement in naming scores at the one year mark ( Abdallah, 2021 , Giovagnoli, 2016 ), it is possible that our cohort includes patients who have successfully adapted to the effects of surgery through re-organization of language networks or other compensatory mechanisms. A second possibility is that our cohort differs from previously reported surgical cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, language mapping that finds the involvement of the basal temporal language area involved in this region must be taken into consideration. When this area is resected, a decline in naming is seen and persists across time ( 56 ). Figure 3 depicts a case that exemplifies the SEEG vision of TLE.…”
Section: Presurgical Cortical Stimulationmentioning
confidence: 99%